2009
DOI: 10.1021/ja908721t
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Based Metal−Organic Nanofibers

Abstract: Long chiral metal-organic nanofibers can be grown using conventional coordination chemistry and biologically derived components in a diffusion controlled growth procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 28 publications
(25 reference statements)
3
91
0
1
Order By: Relevance
“…These unique interactions give rise to multifunctional molecular materials with optical properties, electronic conductivity, magnetism and numerous others. Recently, a great attention is given to designed nanoscale ICPs with different morphologies such as spheres (Sun, Dong, & Wang, 2005;Champness, 2009;Imaz, Hernando, Molina, & Maspoch, 2009), cubes (Jung, & Oh, 2008), rods (Farha et al 2009;Rieter, Taylor, An, Lin, & Lin, 2006), wheels and nanofibres (Imaz, Martí nez, Saletra, Amabilino, & Maspoch, 2009) as they can be easily dispersed in many solvents and exhibit size/shape dependent properties. In particular, nanoscale 0-D and 1-D ICPs, integrated with optical and electrical properties has potential applications in molecular optoelectronics.…”
Section: Introductionmentioning
confidence: 99%
“…These unique interactions give rise to multifunctional molecular materials with optical properties, electronic conductivity, magnetism and numerous others. Recently, a great attention is given to designed nanoscale ICPs with different morphologies such as spheres (Sun, Dong, & Wang, 2005;Champness, 2009;Imaz, Hernando, Molina, & Maspoch, 2009), cubes (Jung, & Oh, 2008), rods (Farha et al 2009;Rieter, Taylor, An, Lin, & Lin, 2006), wheels and nanofibres (Imaz, Martí nez, Saletra, Amabilino, & Maspoch, 2009) as they can be easily dispersed in many solvents and exhibit size/shape dependent properties. In particular, nanoscale 0-D and 1-D ICPs, integrated with optical and electrical properties has potential applications in molecular optoelectronics.…”
Section: Introductionmentioning
confidence: 99%
“…While this manuscript was under review, a very interesting paper was published that reports nanofibers from the controlled diffusion of Cu(II) ions into a solution containing NaOH and dor l-aspartic acid [80]. Extremely long (centimeters), well-defined nanofibers with diameters of 100-200 nm were obtained and imaged by TEM.…”
Section: Other Nanofibersmentioning
confidence: 99%
“…Up to now, various types of biomolecules, such as nucleotides [34], proteins [35], peptides [36], amino acids [37] and nucleobases [38] have been used as the ligands to construct CPs. It also has been demonstrated that some CPs are capable of adsorbing and entrapping a broad range of molecules, due to their good biocompatibility and porosity [34,39].…”
Section: Introductionmentioning
confidence: 99%